The interplay of secondary EFL teachers’ pedagogical beliefs and pedagogical content knowledge with their instructional material use approach orientation - Nurul Fitriyah Almunawaroh; János Steklács (Heliyon)
Teachers' cognitive abilities and affective-motivational characteristics were found to be predictive of their instructional activities in earlier studies. However, limited studies have investigated how these abilities and characteristics interact to determine different approaches to using instructional materials. This study examined how pedagogical content knowledge (PCK) and two types of teachers' pedagogical beliefs (PB) – teacher-centered and learner-centered – interact with one another to determine teachers’ approach orientation to using instructional materials (constructivist approach and transmissive approach). Secondary school English as a foreign language (EFL) teachers participated in the survey. The results revealed the salience of teachers' PCK and PB in determining their approach to instructional material use. The findings suggest an approach for researching and supporting teachers' orientation toward instructional material use.